Perubahan Kebijakan Pertahanan Turki Mendukung Keanggotaan Finlandia di North Atlantic Treaty Organization (NATO): Perspektif Reputasi - Sirwan Yazid Bustami (Indonesian Journal of Peace and Security Studies (IJPSS), 2023)
The Russia-Ukraine conflict has raised concerns among the Nordic countries bordering Russia such as Finland, Sweden, Denmark, Iceland, and Norway. Russia’s military invasion in Ukraine and its military aggressiveness in the region threatens regional stability and security of the Nordic countries. As one of the Nordic countries, Finland responded to Russian aggressiveness by joining the North Atlantic Treaty Organization (NATO) to counteract Russia’s security threats in the region. Finnish membership in NATO was rejected by Turkiye as one of the NATO membership veto holders. However, Turkiye changed its defence policy by supporting Finnish membership in NATO. This study aims to analyze the role of reputation in influencing Turkiye’s defence policy change to support Finnish membership in NATO. Using an analytical descriptive research method accompanied by Jonathan Mercer’s reputation theory, this study proposes the main argument that Turkiye’s defence policy change in favor of Finnish membership in NATO was influenced by Turkiye’s reputation factor as a reliable NATO strategic ally. Turkiye endeavours to maintain this reputation as NATO allies are skeptical of Turkish commitment to uphold NATO’s values and principles. Turkish support for Finnish membership in NATO confirms Turkish commitment to NATO enlargement in order to create regional stability and security in Europe.